THE EFFECT OF DISTRIBUTION OF ZAKAT, INFAQ, ALMS (ZIS) AND REGIONAL EXPENDITURE ON POVERTY IN SUMATRA - Nyimas Yovita Fitriani; Wardatul Fara; SYAUQI IRFAN; Ririn Nopiah (International Journal of Economics, Science, and Education, 2024)
Purpose: This research aims to determine the effect of distribution of zakat, infaq and alms (ZIS), grant spending, subsidy spending, and social assistance spending on poverty with unemployment and GDRP per capita as control variables Design/methodology/approach: Using explanatory quantitative methods with multiple linear regression analysis models for panel data from 10 provinces on the island of Sumatra from 2019 - 2021. Findings: The results show that ZIS distribution has a positive and insignificant effect on poverty. Grant spending and unemployment have a positive effect on poverty, while subsidy spending has a significant negative effect on poverty. Research limitations/implications: The limitation of this research is that the amount of zakat distribution has not been evenly distributed from 2019 onwards so that the research is limited to be conducted below that year. Practical implications: Grant spending and unemployment have a positive effect on poverty, while subsidy spending has a significant negative effect on poverty. Paper type: Research paper. Keyword: poverty, ZIS, grant spending, subsidy spending, social assistance spending